A tough, adhesive, self-healable, and antibacterial plant-inspired hydrogel based on pyrogallol–borax dynamic cross-linking. Issue 20 (17th May 2021) - Ma, Chao; Pang, Huiwen; Liu, Hongguang; Yan, Qian; Li, Jianzhang; Zhang, Shifeng
Abstract : Dynamic cross-linking properties of borates and pyrogallol have been utilized to obtain multifunctional hydrogels by integrating adhesiveness, high mechanical strength, self-healing, and antibacterial properties into one system. Abstract : Multifunctional hydrogels that integrate stretchability, adhesion, self-healing, and antibacterial properties may find use in a variety of fields including electronic skin, wound dressings, and wearable devices; however, traditional hydrogels often exhibit short-term adhesiveness, poor mechanical properties, and a lack of antibacterial activity. Herein, a plant-inspired polyacrylamide-soybean protein isolate-pyrogallol/borax (PAM-SPI-P/B) hydrogel has been developed using a facile green method based on dynamic coordination cross-linking between pyrogallol (PG) and borax. The PG–borax dynamic bonds adjusted the network structure of the hydrogels to provide greater structural integrity to the PAM–SPI double network. This hydrogel possessed a high mechanical strength (large elongation up to 760% and compressive strength up to 1.25 MPa at 80% strain), low swelling ratio, and self-healing properties. Inspired by natural polyphenols that contain adhesive molecules, the addition of pyrogallol provided the hydrogel excellent adhesion to various hydrophilic and hydrophobic substrates. And with the inhibition of pyrogallol autoxidation due to the borax protection, the hydrogel showed repeatable and durable adhesion over 20 cycles. The obtained hydrogels also exhibited good antibacterial activities against Escherichia coli and Staphylococcus aureus because they were based on pyrogallol and borax, which have antibacterial properties. Accordingly, we envision that the PAM-SPI-P/B hydrogels have great potential for use in biomimetic tissues and biosensors.